Doctors’ ethical dilemmas at the interface of conventional medicine and traditional & complementary medicine in Malaysia: analysis and recommendations / Helwa Husna Katiman - Katiman, Helwa Husna (2022)
One of the most prominent criticisms levelled towards traditional & complementary medicine (T&CM) is the lack of sufficient proof of quality, safety and efficacy of most T&CM therapies. Furthermore, studies have shown that doctors are often unprepared to discuss or draw appropriate conclusions concerning T&CM. These problems are further compounded by the absence of ethical guidelines for doctors when at the interface of conventional medicine and T&CM. Setting on this background, this study sought to address a gap in local policy and literature by proposing recommendations on ethical practices when doctors are at the interface of conventional medicine and T&CM. The study employed a library-based research method to examine the current development of Malaysia’s T&CM regulatory framework, and it is followed by an analysis of the ethical dilemmas faced by doctors concerning T&CM. The ethical dilemmas analysed focused on the conflict between respect for autonomy and paternalism, issues with the doctor-patient relationship, and emerging issues relating to the promising therapeutic effect of traditional herbal medicine during a pandemic. Following the analysis, this study developed recommendations on the most appropriate ethical practices, which can be divided into three main components. Begin with ‘Pre-Care’ which was intended for relevant stakeholders to make strategic interventions in knowledge dissemination. Following that, ‘During-Care’ encompassed eight pillars of an ethical framework for doctors when at the interface of conventional medicine and T&CM. Finally, ‘Post-Care’ addressed the duty to report harmful or adverse events related to T&CM. This study aimed to assist the medical fraternity and key stakeholders to take necessary interventions by incorporating ethical practices in T&CM, in order to ensure patients receive the utmost benefit while minimising potential harms.